Perspective Chapter: Microinsurance's Quest to Protect the Unprotected, beyond the Bismarck and Beveridge Models - David Mark Dror (Health Insurance Across Worldwide Health Systems, 2024)
This chapter offers a detailed analysis of microinsurance (nowadays often called “inclusive insurance”), an innovative hybrid model combining grassroots initiatives with top-down approaches to reach populations not covered by government-operated social protection systems. With half of the global population, primarily in low and middle-income countries, lacking social protection, the chapter focuses on the potential of microinsurance to address this pressing issue. The commercial microinsurance attempts, often labeled as “insurance for the poor,” have been largely insufficient. An alternative lies in the “Collaborative and Contributive” (C&C) model of microinsurance, which harnesses social forces, typically more compelling than market forces in informal settings, to stimulate demand. The chapter evaluates microinsurance's social and economic impacts, drawing insights from 25 years of progress. It underscores the need for policymakers, international development bankers, and the reinsurance industry to recognize the potential of the C and C model in providing comprehensive insurance to marginalized populations.
Keywords: I13; O17; O19; I38; D71; 330; Microinsurance; Social protection; Informal sector; Collaborative and Contributive model; Health insurance; Financial inclusion; Risk pooling; Community-based health insurance